From “toads” to “princes”—a hermeneutic study of the Chinese translation of Counselling for Toads: A Psychological Adventure - Wang, Huiping (Frontiers in Psychology, 2025)
The translation of psychotherapy texts has received increased attention in recent years. However, there is still insufficient study on the translation of psychotherapy guidebooks. This study aims to investigate the translation of psychotherapy guidebooks under the guidance of Gadamer’s theory of philosophical hermeneutics through a case study of the Chinese translation of Counselling for Toads: A Psychological Adventure. By analyzing two Chinese versions of the book, the study demonstrates how efficient translation can promote the fusion of horizons between the author, the translator, and the target reader. The findings suggest that the translator of psychotherapy guidebooks should first endeavour to expand their horizon by accumulating psychotherapy knowledge to avoid incorrect or insufficient understanding. Then the translator should endeavour to engage in a dialogue with the author/ST and grasp the essence of the key concepts by referring to the entire knowledge structure of psychotherapy. Finally, the translator should strive to render the text as they interpret it in a flexible manner to ensure that the target reader, who may lack psychotherapy knowledge, can fully understand the translated text.